1971
DOI: 10.2136/sssaj1971.03615995003500030036x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soluble and Exchangeable Aluminum on a Soil Bacillus

Abstract: The test organism, a Bacillus species isolated from soil, behaved as a typical cation exchanger having a CEC of 95 meq/100‐g organism (oven‐dry weight). Increasing acidity from pH 6.6 to 4.5 greatly reduced the number of surviving cells suspended for 3 hours in an acetate buffer. Addition of soluble aluminum up to 80 ppm produced no further detrimental effect upon the organism, even though the cell walls of the organism were saturated with aluminum. Exchangeable aluminum in the form of Al‐saturated Wyoming ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This was also shown in studies by Wilson and Stewart (1956). The inhibition of microbes in the acid spoil may not be a direct effect of hydrogen ion concentration alone, since high aluminum levels that were present (Table 1) can also reduce numbers of soil bacteria (Zwarin et al 1971).…”
Section: Discussionsupporting
confidence: 57%
“…This was also shown in studies by Wilson and Stewart (1956). The inhibition of microbes in the acid spoil may not be a direct effect of hydrogen ion concentration alone, since high aluminum levels that were present (Table 1) can also reduce numbers of soil bacteria (Zwarin et al 1971).…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, although no precise biological meaning can be ascribed to measurements of cation exchange capacity, it is of interest that values quoted for common soil bacteria vary between 95 and 340 m-equiv. per 100 g dry weight (Zwarun, Bloomfield and Thomas, 1971;Zwarun and Thomas, 1973) which greatly exceed the 12.3 m-equiv. determined for barley roots (Drake, Vengris and Colby, 1951).…”
Section: Resultsmentioning
confidence: 81%
“…Some microbial populations resist the effects of metals by accumulating them in an extracellular polysaccharide coat or in the cell wall, so that the metals never enter the cytoplasm and, therefore, exert no effect on microbial activities (Tornabene & Edwards, 1972 ;Zwarun et al, 1971) .…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in nitrate production appears to be one of the most common effects (Barth et aL, 1963 ;Edwards & Nussberger, 1947 ;and Mutatker & Pritchett, 1967) . Investigators have also suggested possible defense mechanisms employed by bacteria against metals (Tornabene &Edwards, 1972 andZwarun et al, 1971) . Yet, there are very few studies of microbial-metal interactions in nature .…”
Section: Introductionmentioning
confidence: 99%